Reconstructing Higher Education in the Post-COVID-19 Period: A Lesson from Zimbabwe Open University - Mswazie Jonathan; Shumba Sibiziwe (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2022)
This study sought to determine potent policy tools which can be utilized as levers in reconstructing higher education landscapes that have been devastated by the COVID-19 pandemic. Three key participants were purposivelselected for the in-depth interviews of the study. The sample consisted of a former minister of Higher and Tertiary Education in Zimbabwe and two current Regional Directors of Zimbabwe Open University (ZOU) from Harare and Bulawayo regions. The study utilized the qualitative case study research design and a literature review to collect data to address the research question. The concept of hard and soft policy instruments and the Intervention Taxonomy were utilized as conceptual guides in data collection and the interpretation of results. The study results reveal that serious resistance to curriculum change and innovation in higher education can be overcome through the effective use of policy instruments. Policy tools can be utilized effectively and efficaciously to scale implementation barriers such as entrenched elitist cultures and practices, which are characteristic of higher education landscapes. More precisely, the study discovered that prudent and innovative application of a mix of hard and soft policy tools or instruments could effect sustainable and durable change. In view of this, the study recommends the use of policy tools as key levers in transforming and reconstructing higher education curricula and systems worldwide.